A centralised telephone service for tobacco cessation: the California experience. (1st June 2000) - Zhu, Shu-Hong; Anderson, Christopher M; Johnson, Cynthia E; Tedeschi, Gary; Roeseler, April
Abstract : OBJECTIVE: To provide an overview of the California Smokers' Helpline, an increasingly popular telephone program for tobacco cessation in California since 1992. As many states, regions, and nations are contemplating various telephone programs as part of large scale anti-tobacco campaigns, this paper presents a practical model. DESIGN: The Helpline provides Californians with free cessation services that include counselling, self help quit kits, and cessation related information. Services are provided in six spoken languages plus a line for the hearing impaired. The program is promoted statewide by media campaigns, health care providers, local tobacco control programs, and the public school system. SETTING: The Helpline is centrally operated through the University of California, San Diego and provides services statewide via telephone. RESULTS: The Helpline has served over 100 000 tobacco users and has become the chief cessation resource for the Comprehensive Tobacco Control Program in California. Media was the most important referral source for Helpline callers (50%), followed by health care providers (20%). About one third of the callers were ethnic minorities and 17% were 24 years old or younger. Compared to California smokers in general, the callers were more dependent on nicotine and more likely to live with other smokers, but they were also more likely to have tried to quit recently and were more ready to try again. Two randomised trials have demonstrated the efficacy of the Helpline's counselling protocol. CONCLUSION: A centralised helpline operation can be an accessible and effective service for tobacco users and should be included in any large scale, comprehensive tobacco control program.